Formic Acid Formation by Clostridium ljungdahlii at Elevated Pressures of Carbon Dioxide and Hydrogen - Oswald, Florian; Stoll, I. Katharina; Zwick, Michaela; Herbig, Sophia; Sauer, Jörg; Boukis, Nikolaos; Neumann, Anke (Frontiers in Bioengineering and Biotechnology, 2018)
Low productivities of bioprocesses using gaseous carbon and energy sources are usually caused by the low solubility of those gases (e. g. H2 and CO). It has been suggested that increasing the partial pressure of those gases will result in higher dissolved concentrations and should therefore be helpful to overcome this obstacle. Investigations of the late 1980s with mixtures of hydrogen and carbon monoxide showed inhibitory effects of carbon monoxide partial pressures above 0.8 bar. Avoiding any effects of carbon monoxide, we investigate growth and product formation of Clostridium ljungdahlii at absolute process pressures of 1 bar, 4 bar and 7 bar in batch stirred tank reactor cultivations with carbon dioxide and hydrogen as sole gaseous carbon and energy source. With increasing process pressure the product spectrum shifts from mainly acetic acid and ethanol to almost only formic acid at a total system pressure of 7 bar. On the other hand, no significant changes in overall product yield can be observed. By keeping the amount of substance flow rate constant instead of the volumetric gas feed rate when increasing the process pressure, we increased the overall product yield of 7.5 times of what has been previously reported in literature. After 90 h of cultivation at a total pressure of 7 bar at total of 4 g L-1 of products is produced consisting of 82.7 % formic acid, 15.6 % acetic acid and 1.7 % ethanol.